Thermogravitational Convective Flow and Energy Transport in an Electronic Cabinet with a Heat-Generating Element and Solid/Porous Finned Heat Sink - Xuan Hoang Khoa Le; Ioan Pop; Mikhail A. Sheremet (Mathematics, 2021)
Heat transfer enhancement poses a significant challenge for engineers in various practical fields, including energy-efficient buildings, energy systems, and aviation technologies. The present research deals with the energy transport strengthening using the viscous fluid and solid/porous fins. Numerical simulation of natural convective energy transport of viscous fluid in a cooling cavity with a heat-generating element placed in a finned heat sink was performed. The heat-generating element is characterized by constant volumetric heat generation. The Darcy–Brinkman approach was employed for mathematical description of transport processes within the porous fins. The governing equations formulated using the non-primitive variables were solved by the finite difference method of the second-order accuracy. The influence of the fins material, number, and height on the flow structure and heat transfer was also studied. It was found that the mentioned parameters can be considered as control characteristics for heat transfer and fluid flow for the cooling system.